Right idea, wrong magnitude system. (2017) - Lourenco, Stella F.; Aulet, Lauren S.; Ayzenberg, Vladislav; Cheung, Chi-Ngai; Holmes, Kevin J.
Abstract: Leibovich et al. claim that number representations are non-existent early in life and that the associations between number and continuous magnitudes reside in stimulus confounds. We challenge both claims – positing, instead, that number is represented independently of continuous magnitudes already in infancy, but is nonetheless more deeply connected to other magnitudes through adulthood than acknowledged by the "sense of magnitude" theory.